Linear-complexity algorithms for QoS support in input-queued switches with no speedup. - Kam, A.C.
We present several fast, practical linear-complexity scheduling algorithms that enable provision of various quality-of-service (QoS) guarantees in an input-queued switch with no speedup. Specifically, our algorithms provide per-virtual-circuit transmission rate and cell delay guarantees using a credit-based bandwidth reservation scheme. Our algorithms also provide approximate max-min fair sharing of unreserved switch capacity. The novelties of our algorithms derive from judicious choices of edge weights in a bipartite matching problem. The edge weights are certain functions of the amount and waiting times of queued cells and credits received by a virtual circuit. By using a linear-complexity variation of the well-known stable-marriage matching algorithm, we present theoretical proofs and demonstrate by simulations that the edge weights are bounded. This implies various QoS guarantees or contracts about bandwidth allocations and cell delays. Network management can then provide these contracts to the clients. We present several different algorithms of varied complexity and performance (as measured by the usefulness of each algorithm's contract). While most of this paper is devoted to the study of ?soft? guarantees, a few ?hard? guarantees can also be proved rigorously for some of our algorithms. As can be expected, the provable guarantees are weaker than the observed performance bounds in simulations. Although our algorithms are designed for switches with no speedup, we also derive upper bounds on the minimal buffer requirement in the output queues necessary to prevent buffer overflow when our algorithms are used in switches with speedup larger than one
Keywords: QoS guarantees; QoS support; Approximate max-min fair sharing; Bandwidth allocations; Bipartite matching problem; Bounded edge weights; Buffer overflow prevention; Cell delay guarantees; Cell delays; Contracts; Credit-based bandwidth reservation; Credits; Hard guarantees; Input-queued switches; Linear-complexity scheduling algorithms; Minimal buffer requirement; Network management; Output queues; Packet switching; Per-virtual-circuit transmission rate; Performance; Performance bounds; Quality-of-service.; Queued cells; Simulations; Soft guarantees; Stable-marriage matching algorithm; Unreserved switch capacity; Upper bounds; Virtual circuit; Waiting times